Inovasi Pembelajaran E-Learning Dalam Menghadapi New Normal Di SMK Negeri 1 Lawang Wetan - Sulistiawati Sulistiawati; Lukman Hakim; Patricia Hotma Minar Lubis; Rita Sulistyowati; Sugiarti Sugiarti; Lefudin Lefudin (Wahana Dedikasi : Jurnal PkM Ilmu Kependidikan, 2021)
The conditions of the Covid-19 pandemic created conditions that seemed to be "forced" to transform and adapt drastically in learning from home through online media (on line). Various learning media applications are already available, both government and private. The government issued a Circular of the Minister of Education and Culture Number 9/2018 concerning the Utilization of Learning Houses. The private sector also provides online tutoring such as the teacher room, Zenius, Klassku, Kahoot, and others. Teachers are required to be more creative and innovative in implementing learning in schools. Therefore, it is necessary to hold a learning training for teachers to motivate them to carry out their obligations as educators. The counseling had the theme "Innovation of e-learning in Facing the New Normal at SMK Negeri 1 Lawang Wetan Musi Banyuasin". Participants were 36 teachers of SMK 1 Lawang Kidul Musi Banyuasin. The material presented was responded enthusiastically by the training participants. This can be seen from the questions asked by the participants and the results of the questionnaires given. The questionnaire used a Likert scale with an overall average of 4.47. This means that most participants strongly agree with the education and training provided. The messages and impressions presented by the participants were also very positive